(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
supporting and empowering women in Libyan society, consolidating their human rights, and spreading the legal culture, especially with regard to women’s rights. Providing support by developing women’s skills and training. To achieve this goal, the study presented and analyzed some models of social centers and women’s associations within the local community in the city of Misrata, arriving at a proposed vision for increasing and activating social centers to support and empower women, through a number of points